Pengaruh Suhu Terhadap Hatching Rate Dan Survival Rate Pada Pemijahan Ikan Nila (Orechromis Niloticus) Menggunakan Sistem Inkubator - Ma’ruf, Mohammad Bashitul; Ernawati (Jurnal Perikanan dan Kelautan, 2025)
This study aims to examine the effect of temperature variations on the hatching rate and survival rate of Nile tilapia (Oreochromis niloticus) larvae using an incubator system. The experimental method involved three temperature treatments: 26°C, 28°C, and 30°C. Parameters observed included hatching rate and survival rate over a six-day incubation period. The results showed that 28°C yielded the highest hatching rate at 51%, followed by 26°C at 22%, while no hatching occurred at 30°C. However, the survival rate across all treatments was recorded at 100%, indicating that larvae that hatched were able to survive well in the incubation environment. It can be concluded that temperature significantly affects the hatching success of Nile tilapia eggs, with the optimal incubation temperature being 28°C. These findings are expected to serve as a reference for improving hatchery efficiency through optimal temperature control in incubator systems.